The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/2317-1545v44264545
|View full text |Cite
|
Sign up to set email alerts
|

SARS software for analysis of radiographic images of Urochloa decumbens (Stapf) RD Webster seeds

Abstract: Recently is growing the need for non-invasive, fast, and accurate technologies that can predict seed quality. Between these technologies, X-ray image analysis stand out for evaluation of the internal morphology of the seeds. Thus, the aim of the present study was to evaluate the efficiency of a specialized software for analyzing digital radiographs of Urochloa decumbens seeds called SARS (Sistema de Análise de Radiografias de Sementes - Seed Radiograph Analysis System). Five comercial seed lots of U. decumbens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(29 reference statements)
0
2
1
1
Order By: Relevance
“…Unlike what was observed in this study, Ramos et al (2022) observed that U. decumbens seeds with higher germination potential and vigor showed significant correlations with some of the physical variables obtained by the X-ray test, such as area, perimeter, and tissue density. Furthermore, as already mentioned, several other studies have demonstrated the benefit of osmopriming when compared to unprimed seeds.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike what was observed in this study, Ramos et al (2022) observed that U. decumbens seeds with higher germination potential and vigor showed significant correlations with some of the physical variables obtained by the X-ray test, such as area, perimeter, and tissue density. Furthermore, as already mentioned, several other studies have demonstrated the benefit of osmopriming when compared to unprimed seeds.…”
Section: Resultscontrasting
confidence: 99%
“…Medeiros et al (2020) evaluated the analysis of X-ray images on U. ruziziensis seeds and observed that physical attributes obtained by the X-ray test such as tissue density and seed filling were highly correlated with physiological quality, efficiently helping to carry out their large-scale phenotyping. The physical attributes obtained by the X-ray technique in U. decumbens seeds were highly correlated with germination and vigor, showing the potential of the technique for this species (Ramos et al, 2022).…”
Section: Introductionmentioning
confidence: 88%
“…The study in [66] used the Ilastik tool to categorize voids, fractures, and mineral grains in sandstone samples from Antarctica's McMurdo Dry Valleys. In [67] Ilastik was used to analyze seedling images, efficiently classify seed vigor, and demonstrate its capability to assess physiological potential within a short 7-day germination period. The researchers demonstrated in [68] that cisTEM's GPU-accelerated 2D template matching provides computational efficiency and scalability, enabling precise ribosome identification in Mycoplasma pneumoniae cells.…”
Section: Related Workmentioning
confidence: 99%
“…Neste contexto, sementes do gênero Urochloa tem sido objeto de estudos recentes com processamento de imagens, através do qual dados biométricos das sementes são relacionados a suas informac ¸ões fisiológicas, e.g. porcentagem de germinac ¸ão, velocidade de emergência [Ramos et al 2022, de Freitas et al 2021. Em particular, imagens de raios X de Urochloa brizantha tem sido utilizadas para verificar a ocorrência de danos nas sementes durante seu beneficiamento [Silva et al 2022, Jeromini et al 2019.…”
Section: Introduc ¸ãOunclassified